Can Community Policing Reduce the Chilling Effect of Immigration Enforcement on Latinx Crime Reporting? Evidence from Los Angeles - Muchow, Ashley N. (Crime & delinquency, 2024)
While scholars have linked immigration enforcement with reductions in Latinx crime reporting, little research has examined the tools localities can use to counter reporting declines. This study assesses whether a community policing program adopted by the Los Angeles Police Department (LAPD) offset documented decreases in Latinx domestic violence reporting after President Trump assumed office. Using data on crimes reported to the LAPD between 2014 and 2019, this study finds that while domestic violence reports made by Latinx victims declined elsewhere after Trump took office, they increased in areas exposed to the community policing program. Results suggest that community policing may be a viable tool to encourage help-seeking behavior among residents vulnerable to deportation.